Controllers' use of informational tactics. Issue 6 (19th September 2018) - Goretzki, Lukas; Lukka, Kari; Messner, Martin
Abstract : Controllers typically have a 'dual accountability' towards the finance function and operational management, respectively. This dual accountability at times confronts them with conflicting expectations. In this paper, we suggest that 'informational tactics' constitute an important resource which controllers rely on so as to handle these expectations and to successfully present themselves vis-à-vis their different internal stakeholders. Drawing upon interview data, we demonstrate that informational tactics relate to different dimensions of information control (i.e. 'when', 'how' and 'what' information is to be exchanged) and that they depend on the respective room for manoeuvre a controller has in a given situation. Overall, our analysis adds a more nuanced picture to the literature on controllers' handling of information and demonstrates the fundamental role of informational tactics for their everyday work.